Using wavelets in applied electromagnetics : an algorithm for efficient pattern synthesis of linear aperture antennas - Cuiñas Gómez, Íñigo; Landesa, Luis; Rodríguez Pino, Marcos (Pro Mathematica, 1998)
Pattern synthesis of linear aperture antennas is a classical problem in Applied Electromagnetics with a great number of resolving methods. In this paper, a new algorithm that uses wavelets to compute the solution is presented. The new method reaches a good approximation of the aperture field from the antenna radiation pattern, using the Haar wavelet basis. Results prove the performance of the proposed method.